Answer: x^4
Step-by-step explanation:
1. Rewrite the expression in fraction form:
(3√x²)^6 = x^(2/3)^6
2 is the exponent, so when written in fraction form, it is the numerator. 3 is the index or root, so in fraction form it is the denominator.
2. Solve:
x^(2/3)^6 = x^(12/3) = x^4
Because the exponent 2/3 is raised to the power of 6, you can use the power rule, which basically just means that whenever an exponent is raised to an exponent, multiply them. So, 2/3 * 6 equals 12/3, and 12/3 equals 4, making your answer x^4.
Answer:
All corresponding sides and angles will be congruent
Step-by-step explanation:
What is the answer to this wrok
Answer:
A(t)= 18000(0.988)^t
Step-by-step explanation:
Given data
Ryan bought a brand new car for $18,000
Its value depreciated at a rate of 1.2%
Let us use the compound expression
A= P(1-r)^t
substitute
A= 18000(1-0.012)^t
A(t)= 18000(0.988)^t
Hence the expression is A(t)= 18000(0.988)^t